Exploring the Mediating Role of Financial Stability in the Relationship Between FinTech and Bank Performance: Evidence from the MENA Region - Karoui, Chedia (Journal of Ecohumanism, 2025)
This study examines the impact of FinTech and financial stability on bank performance in the MENA region. Using a sample of 100 commercial banks from the MENA region over the period from 2010 to 2022, we apply hierarchical regression models to test several hypotheses. Our results show that FinTech significantly enhances both Return on Assets (ROA) and Return on Equity (ROE), suggesting that financial innovation improves bank performance by expanding service offerings, enhancing risk management, and optimizing resource allocation. Moreover, the study finds that financial stability plays a key role in boosting bank performance, supporting the idea that stable financial environments contribute to the profitability of banks. The mediation analysis reveals that financial stability fully mediates the relationship between FinTech and bank performance, indicating that the positive effect of FinTech on performance is largely channeled through improved financial stability.